Understanding hand hygiene behaviour in the intensive care unit to inform interventions: an interview study - Lambe, Kathryn (BMC Health Serv Res, 2020)
BACKGROUND: Improving hand hygiene (HH) compliance is one of the most important, but elusive, goals of infection control. The purpose of this study was to use the capability (C), opportunity (O), motivation (M), and behaviour (B; COM-B) model and the theoretical domains framework (TDF) to gain an understanding of the barriers and enablers of HH behaviours in an intensive care unit (ICU) in order to identify specific interventions to improve HH compliance. METHODS: A semi-structured interview schedule was developed based upon the COM-B model. This schedule was used to interview a total of 26 ICU staff: 12 ICU nurses, 11 anaesthetic specialist registrars, and three anaesthetic senior house officers. RESULTS: Participants were confident in their capabilities to carry out appropriate HH behaviours. The vast majority of participants reported having the necessary knowledge and skills, and believed they were capable of carrying out appropriate HH behaviours. Social influence was regarded as being important in encouraging HH compliance by the interviewees- particularly by nurses. The participants were motivated to carry out HH behaviours, and it was recognised that HH was an important part of their job and is important in preventing infection. It is recommended that staff are provided with targeted HH training, in which individuals receive direct and individualised feedback on actual performance and are provided guidance on how to address deficiencies in HH compliance at the bedside at the time at which the HH behaviour is performed. Modelling of appropriate HH behaviours by senior leaders is also suggested, particularly by senior doctors. Finally, appropriate levels of staffing are a factor that must be considered if HH compliance is to be improved. CONCLUSIONS: This study has demonstrated that short interviews with ICU staff, founded on appropriate behavioural change frameworks, can provide an understanding of HH behaviour. This understanding can then be applied to design interventions appropriately tailored to the needs of a specific unit, which will have an increased likelihood of improving HH compliance.